THE EFFECT OF VARIATIONS OF CHITOSAN BIOCOAGULANTS FROM MUJAIR (Oreochromis mossambicus) FISH SCALE WASTE IN REDUCING VEHICLE WASH WATER POLLUTION - Arfi, Febrina; Mufliha, Varisa (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Car wash services in Indonesia are becoming increasingly popular in urban areas. One of them is a vehicle washing business in Kuta Raja District, Banda Aceh. However, vehicle washing services not only increase regional income, but also produce vehicle washing liquid waste which can reduce environmental quality. So it is necessary to process liquid waste, one of which is by using tilapia fish scale chitosan. This research aims to determine the value of the best coagulant dose of chitosan mass in reducing COD, TSS and Phosphate pollutants in vehicle washing waste. The dose determination method is carried out by varying the dose to 10 mg/L, 20 mg/L and 30 mg/L for each with a combination of fast stirring at 120 rpm for 30 minutes and slow stirring at 90 rpm for 40 minutes. The results of the study showed that the best dose for reducing COD parameters was the use of a dose of 20 mg/L, then the best mass for reducing TSS parameters was the use of a dose of 30 mg/L and the effectiveness of reducing COD levels were 81.53%, then the reduction in TSS levels was 88.11%. . In phosphate there is an increase in concentration with each dose given. The addition of chitosan to COD, TSS and Phosphate depends on the optimum dose found in vehicle washing wastewater. Thus, processing vehicle washing liquid waste using tilapia fish scale chitosan using the flocculation-coagulation method is able to reduce the concentration of the parameters.